Language use in 'Loin du Périph': A sociopragmatic study of characters - Nurfairuz, Muhammad Rizkyanca; Hardini, Tri Indri; Gumilar, Dudung (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2023)
This study investigates the antagonistic behaviour of Alice –as someone who is in favour of extreme-right wing authority–, who initially conceals her support for the dominance of the extreme right-wing party that espouses white supremacy ideology in her interaction with Ousmane as someone who has affected by racism and discrimination. As film progresses, there is a change in her attitude from being concealed to being openly supportive of the ideology of the right-wing or even far-right party, which does not favour pluralism, immigrants, and non-white people, also known as xenophobia. Regarding Alice's behaviour, all of her speech acts will be analysed using Pragmatics-Sociolinguistics theory. It is hoped that by using Pragmatics-Sociolinguistics theory, the behavior and speech acts of the character Alice can be explained and analyzed.